Severe course of herpes simplex virus, Staphylococcus aureus and Acinetobacter infection in a patient with atopic dermatitis after delivery - Lis, Anna; Krauze, Ewa; Pierzchała, Ewa; Kamińska, Grażyna; Brzezińska-Wcisło, Ligia (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2003)
There are many immune system disturbances in the course of atopic dermatitis. In the prominent part of patients this may contribute to the increased incidence of bacterial and viral infection. We report a case of a 23-year-old patient with atopic dermatitis, who developed generalized herpetic lesions all over her body during the 1st month after delivery, blood cultures were positive for growth of Staphylococcus aureus and Acinetobacter sp. Antibiotic and antiviral therapy resulted in the improvement of the general condition and disappearance of herpetic lesions. Because pregnancy and delivery are considered predisposing factors for the development of various infections, we propose the appropriate prophylaxis in such cases.